(untitled) (Bulletin KNOB, 2009)
The question whether urban-planning considerations played a part in the planning process around the Amsterdam town hall in the seventeenth century has not been answered satisfactorily so far. In 1919 A. Boeken made a reconstruction of the resolutions of the Amsterdam town council, also in an attempt to explain the blending in of the building with its context. This reconstruction is still the convention, but it contains a number of incongruities, notably the somewhat oblique position of the building in relation to Dam square, so that an orthogonal plot was not possible. This is peculiar because all the well-known designs for the town hall are rectangular. Boeken also founded his reconstruction on the basis of documents that are not mentioned in the resolutions. However, an accurate reading of the – frequently cryptic – resolutions offers sufficient clues for a new reconstruction that answers many of the current questions. Evidently it is likely that the Amsterdam town council already intended to erect a rectangular, classicist building in a monumental position on Dam square from the very start of the design process in 1639, but at any rate from 1642 onwards. This new reconstruction also sheds new light on a drawing from 1643, including a worked-out design for a town hall, signed by the town land surveyor Cornelis Danckerts de Rij. So far, it was hard to find a connection between this drawing and the resolutions, but in spite of the fact that the measurements of the building are different from those mentioned in the texts, the information from this drawing undoubtedly fits in with the ambitions of the town council concerning the character and position of its new town hall. The reconstruction paves the way for a reassessment of the Amsterdam town council as a commissioner with an eye for the spatial qualities of the town centre and how these could be improved through its actions.